Hepatic Blood Flow with Colloidal 198Au in the Diagnosis of Chronic Hepatitis in Children - Marian, Lidia; Szantay, Viorica (Nuklearmedizin - NuclearMedicine, 1975)
Tracer quantities of colloidal 198Au were used to estimate the hepatic blood flow in normal children and in children with active or progressive chronic hepatitis and also to obtain scintigrams of the liver.In active chronic hepatitis a significant decrease in HBF values was observed, suggesting that the method may be used as a diagnostic criterion which is superior to hepatic scintigraphy.In progressive chronic hepatitis HBF values even lower than those in active hepatitis were observed. Together with more characteristic clinical findings and abnormal results of biochemical function tests, they underline the value of the method in estimating the severity and the evolution of the disease.